Capital stock in Spain and its distribution by territories (1964-2012) - Mas, Matilde; Perez, Francisco; Uriel, Ezequiel (REGION, 2015)
Since 1995 the BBVA Foundation and the Ivie have been conducting an extensive research program on Spanish economic growth. The regularly-updated database "Capital stock in Spain and its distribution by territories" are the basis of this program, providing information on the accumulation of capital in Spain over the last four decades.